(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
Cardiovascular computed tomography (CCT) is an important imaging modality in congenital and acquired heart diseases in children. Technological advances have led to significant improvements in the spatial and temporal resolution of ККТ, accompanied by increased data acquisition speed and reduced radiation exposure. This has transformed ССT from a rarely used technique into an essential diagnostic tool, applied alongside echocardiography, cardiovascular MRI, and invasive angiography in daily multidisciplinary diagnostic practice. The use of CCT in congenital and acquired pediatric heart diseases may present both technical and diagnostic challenges. This review highlights key aspects of the current state-of-the-art ККТ capabilities across the spectrum of pediatric cardiac pathologies.